2014
DOI: 10.11648/j.jgo.20140203.12
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean Section and Associated Factors at Mizan Aman General Hospital Southwest Ethiopia

Abstract: Abstract:Background: It is estimated that about 20 million cesarean section (CS) deliveries occur each year in the world.But, in least developed countries the rate of deliveries by CS is very few. Objectives: The objective of this study is to assess Factors associated with Caesarean section at Mizan Aman General Hospital Southwest Ethiopia. Method: A cross sectional study was conducted by reviewing medical record of mothers. The sample size was determined using single population proportion and total sample siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
27
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 13 publications
9
27
2
1
Order By: Relevance
“…A national survey in Ethiopia is also comparable with this study showing that the overall institutional caesarean rate in public sectors was 15% [9]. The result in this study was lower than the finding in Mizan Aman hospital, Southwest Ethiopia (21%) and Addis Ababa (21.5%) [17,18]. This discrepancy could be explained by the difference in the study areas, and access to the services.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…A national survey in Ethiopia is also comparable with this study showing that the overall institutional caesarean rate in public sectors was 15% [9]. The result in this study was lower than the finding in Mizan Aman hospital, Southwest Ethiopia (21%) and Addis Ababa (21.5%) [17,18]. This discrepancy could be explained by the difference in the study areas, and access to the services.…”
Section: Discussionsupporting
confidence: 79%
“…The study also showed that mothers aged 35 and above had higher odds of delivering by caesarean section. This finding is supported by the study conducted in Mizan Aman hospital, Southwest Ethiopia [17].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This discrepancy might be due to differences in the study area and most of the above study was conducted in specialized referral teaching hospitals [16][17][18][19][20]. Our survey finding was also far below the global figure, North America (32.3%), Oceania (31.1%), Europe (25%), Asia (19.2%) but above the African rate of CS (7.3%) [21].…”
Section: Discussionmentioning
confidence: 57%